A THEORETICAL VIEW OF THE STRUCTURAL TRANSFORMATION OF LITERARY GENRES IN THE FACE OF THE DEVELOPMENT OF MASS MEDIA: THE CASE OF TURKISH LITERATURE - Cem Yılmaz BUDAN (Езиков свят)
The theoretical debates made around the interaction of mass media with literary production contributed to the formation of a lively and fertile intellectual infrastructure of the Turkish criticism of the Republican era. The transformative effect of the unpredictable development of certain mass media, especially cinema, radio and television, on the normative structures of literary genres such as novels, theater and stories is the focus of these discussions. The rapid expansion of the boundaries of mass media's sphere of influence and it’s becoming the primary preoccupation shaping the daily life practices of individuals has led Turkish writers to doubt the future of ancient literary genres. However, these concerns, which were voiced more vehemently during the first half of the 20th century, gradually gave way to the search for the contexts in which literary genres could benefit from mass media. In this study, based on the approaches of critics who have expressed their opinions about the relationship between mass media and established narrative forms, the chronological development of the literature shaped specifically for the subject will be revealed and the metamorphosis of the dominant discourse developed in the face of the problem discussed will be analyzed. Another aim of the study is to ensure that the questions of in which contexts mass communication technologies transform the forms and qualities of literary products and whether these instruments will cause the intellectual need for genres such as novels and theater to disappear are discussed in the axis of the approaches of the critics.